Trends in Colloid and Interface Science XXIII - Bucak, Seyda. (Progress in Colloid and Polymer Science, 2010)
This volume includes 11 contributions to the 23rd Conference of the European Colloid and Interface Society which took in Antalya, Turkey between September 6th and 11th, 2009. The contributions from leading scientists cover a broad spectrum of topics concerning• Self Assembly• Interfacial Phenomena• Colloidal Dispersions and Colloidal Stability• Polymer Solution, Gels and Phase Behaviour• Nanostructured Materials• Biomaterials and Medical AspectsDue to the increasing significance of Colloid and Interface Science for both scientific and technical applications where scientific principles also contribute to new technologies in fast improving Nanotechnology and Medical Science, this book will be an essential source of information with respect to recent developments and results related to this field.